(3GdbhI GdJfXjejI (B:s (3Hjf GdfXQjI h GdJWHjb (B/s - (3GdSGde, eDjO SYjOs ((3YeGf(B: s (3GKQGA(B, s, 2009)
(3ebOeI aj GdbhI GdJfXjejI , GdYdGbI Hjf GdbhI h GdSdWI h GdJCKjQ , GdHYO GdYehOj h GdCabj ddbhI GdJfXjejI , GdfJGFL GdJfXjejI h GdSdhcjI dgjcd GdbhI (B((3GdUQGY GdJfXjej(B) (3, GdGZJQGH GdJfXjej , GdSdhc GdSjGSj aj GdefXeI , GdbhI GdJfXjejI aj GdGOGQI GdGSJQGJjLjI , OQGSGJ YQHjI aj eLGd GdbhI GdJfXjejI (B.s
(3eQGLY (B: (3dcd aUd eQLYs
Keywords: (3GdEOGQIs; (3GdJfXjes; (3GdefXeGJs; (3JfXje hEOGQIs